Death is that man taking names : intersections of American medicine, law, and culture - Burt, Robert A., 1939-2015 (California/Milbank books on health and the public, 2002)
The American culture of death changed radically in the 1970s. For terminal illnesses, hidden decisions by physicians were rejected in favor of rational self-control by patients asserting their "right to die"--Initially by refusing medical treatment and more recently by physician-assisted suicide